2019
DOI: 10.31616/asj.2018.0228
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Feasibility of Full Endoscopic Decompression in One- to Three-Level Lumbar Canal Stenosis via a Single Skin Port Using a New Endoscopic System, Percutaneous Stenoscopic Lumbar Decompression

Abstract: Study Design This retrospective study involved 450 consecutive cases of degenerative lumbar stenosis treated with percutaneous stenoscopic lumbar decompression (PSLD). Purpose We determined the feasibility of PSLD for lumbar stenosis at single and multiple levels (minimum 1-year follow-up) by image analysis to observe postoperative widening of the vertebral canal in the area. Overview of Literature The decision not to perform an endoscopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The study showed statistically significant improvement ODI and VAS pain scores for leg and back pain postoperatively compared to that before surgery. These were a constant finding in published literature after endoscopic stenosis decompression either for PSLD 27 or any endoscopic decompressive techniques.…”
Section: Rationale Of the Inside-out Approachmentioning
confidence: 76%
See 1 more Smart Citation
“…The study showed statistically significant improvement ODI and VAS pain scores for leg and back pain postoperatively compared to that before surgery. These were a constant finding in published literature after endoscopic stenosis decompression either for PSLD 27 or any endoscopic decompressive techniques.…”
Section: Rationale Of the Inside-out Approachmentioning
confidence: 76%
“…25 The full-endoscopic lumbar technique for operating spinal canal stenosis is used today as a largely standard procedure and allows sufficient decompression. 26 In this study, we described in detail the inside-out approach of performing lumbar endoscopic unilateral laminotomy with bilateral decompression (LE-ULBD), one of the ways of performing percutaneous stenoscopic lumbar decompression (PSLD), 27 to address 1 level lumbar spinal stenosis and determined its outcome after 12-month follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…In the authors' opinion, the style used in the literature for interlaminar endoscopic decompression for spinal stenosis can be further divided into inside-out, outside-S100 www.e-neurospine.org in technique and contralateral approach. [8][9][10] The outside-in technique of decompression is what is described as over the top decompression in minimally invasive literature for both microscopic and endoscopic surgery. [11][12][13] The authors defined outsidein technique of endoscopic stenotic decompression as bony decompression of cephalad lamina, caudal lamina, inferior articular process, and superior articular process ("outside") to the extent that is sufficient for complete release of ligamentum flavum prior to removal of ligamentum en bloc with blunt instrument in the last part of the procedure to expose the spinal canal ("in").…”
Section: Introductionmentioning
confidence: 99%
“…The inside-out technique, on the other hand, involved bony decompression of lamina, inferior articular process, and superior articular process with early splitting of ligamentum flavum to get into spinal canal ("inside") prior to releasing ligamentum flavum from within the spinal canal with concurrent bony decompression ("out"). 10 Contralateral appro ach involved sparing ipsilateral ligamentum flavum and bony structure, creating sublaminar window working space in the contralateral lamina and performing contralateral ligamentum flavum resection and foraminotomy. 8,9,14,15 This review focus on LE-ULBD outside-in approach which is commonly known as over the top decompression technique.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, endoscopic decompression surgery has been used to treat central canal stenosis 7 and other kinds of lumbar degenerative stenosis using newly designed endoscopes, with shorter and wider working channels, and surgical tools. 8 The route approaching down from the skin via the lamina to the epidural space is anatomically more familiar to most spine surgeons than the I-O technique in ETD. However, not a few endoscopic spine surgeons, including Yeung, still place a high value on I-O taking the foraminal route and insist that the ETD might be used for most lumbar spine pathologies, except for those that are unreachable.…”
mentioning
confidence: 99%